2020
DOI: 10.3389/fimmu.2020.01128
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Chimeric Antigen Receptor (CAR) Modified T-Cell Therapy Limitations in Multiple Myeloma

Abstract: Multiple myeloma (MM) remains an incurable disease regardless of recent advances in the field. Therefore, a substantial unmet need exists to treat patients with relapsed/refractory myeloma. The use of novel agents such as daratumumab, elotuzumab, carfilzomib, or pomalidomide, among others, usually cannot completely eradicate myeloma cells. Although these new drugs have had a significant impact on the prognosis of MM patients, the vast majority ultimately become refractory or can no longer be treated due to tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 159 publications
1
25
0
Order By: Relevance
“…A major determinant of successful CAR-T therapy is the identification of the appropriate antigen, which is uniquely and highly expressed by MM cells, in order to avoid adverse events. Specifically, the main challenge of CAR-T therapy is the appropriate target selection, which is critical in the management of on-target, off-tumor toxicity to avoid excess cytokine release after target recognition on non-malignant cells ( 79 ). Similarly, the major on-target, on-tumor adverse events of CAR-T cells include cytokine release syndrome (CRS) characterized by fever, hypotension and/or renal failure, as well as neurotoxicity ( 80 ); and are mainly due to the CAR-T cell activation and expansion and uncontrolled cytokine release ( 79 ).…”
Section: Immunotherapy In MMmentioning
confidence: 99%
See 2 more Smart Citations
“…A major determinant of successful CAR-T therapy is the identification of the appropriate antigen, which is uniquely and highly expressed by MM cells, in order to avoid adverse events. Specifically, the main challenge of CAR-T therapy is the appropriate target selection, which is critical in the management of on-target, off-tumor toxicity to avoid excess cytokine release after target recognition on non-malignant cells ( 79 ). Similarly, the major on-target, on-tumor adverse events of CAR-T cells include cytokine release syndrome (CRS) characterized by fever, hypotension and/or renal failure, as well as neurotoxicity ( 80 ); and are mainly due to the CAR-T cell activation and expansion and uncontrolled cytokine release ( 79 ).…”
Section: Immunotherapy In MMmentioning
confidence: 99%
“…Specifically, the main challenge of CAR-T therapy is the appropriate target selection, which is critical in the management of on-target, off-tumor toxicity to avoid excess cytokine release after target recognition on non-malignant cells ( 79 ). Similarly, the major on-target, on-tumor adverse events of CAR-T cells include cytokine release syndrome (CRS) characterized by fever, hypotension and/or renal failure, as well as neurotoxicity ( 80 ); and are mainly due to the CAR-T cell activation and expansion and uncontrolled cytokine release ( 79 ). Importantly, clinical experience has now shown that targeting interleukin-6 and use of dexamethasone can treat these toxicities ( 23 , 24 , 77 , 81 ).…”
Section: Immunotherapy In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…CD19 expression is usually seen in myeloma stem cells and is absent in mature plasma cells. Premature cells with CD19 expression are responsible for disease progression, drug resistance, relapse, and reduced survival in MM [ 25 ]. CD19 CAR T cells (CTL019) target both CD19 and stem-cell antigens that are co-expressed in myeloma propagating cells (MPC), resulting in a favorable outcome [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…GPRC5D expression is independent of BCMA expression making anti-GPRC5D CAR T cells an alternative therapy in case of relapse after anti-BCMA therapy [ 34 ]. Table 1 summarizes the aforementioned target antigens and their role in CAR T cell therapy [ 8 , 11 , 15 - 17 , 20 - 21 , 25 , 29 , 32 , 34 ].…”
Section: Reviewmentioning
confidence: 99%